Cloning and distribution of galanin-like peptide mRNA in the hypothalamus and pituitary of the macaque - Steiner, Robert A.; Cunningham, Matthew J.; Scarlett, Jarrad M. (Endocrine Society, 2002)
Galanin-like peptide (GALP) is a newly discovered hypothalamic neuropeptide, which is regulated by leptin and implicated in the regulation of GnRH secretion in the rodent. We searched the human genome database and determined that the human GALP gene comprises six exons, as has been shown for human galanin. We used rapid amplification of cDNA ends to clone a full-length cDNA (802 bp) of the macaque homologue of GALP and found it to be highly conserved between human and macaque at both the nucleotide (93%) and peptide (94%) levels. Mature GALP is predicted to be 60 amino acids in the macaque as in other species, and the region of GALP (9-21) that shows homology to the N-terminal 13 amino acids of galanin is perfectly conserved. We mapped the distribution of GALP mRNA in the hypothalamus and pituitary of the macaque by in situ hybridization and observed that, as in rodent species, the expression of GALP mRNA is confined to the arcuate nucleus, median eminence, and neurohypophysis. Using double-label in situ hybridization, we found that nearly all (98%) GALP mRNA-expressing cells in the arcuate nucleus also express mRNA for the long form of the leptin receptor. These findings suggest that a leptin-GALP signaling pathway exists in a primate species.
Keywords: mRNA; hypothalamus; pituitary; macaque; galanin-like peptide; Molecular Sequence Data; Macaca nemestrina; Pituitary Gland, metabolism; RNA, Messenger, biosynthesis; Nerve Tissue Proteins, biosynthesis, metabolism; Amino Acid Sequence; Galanin-Like Peptide; Research Support, U.S. Gov't, P.H.S.; Animals; RNA Probes; Humans; Hypothalamus, metabolism; Gene Amplification; Base Sequence; Cloning, Molecular